El debido proceso en la audiencia de calificación de flagrancia y el procedimiento directo - Fierro Yánez, Fredy Fernando (2021)
This thesis work for obtaining the master's degree entitled: "THE DUE PROCESS IN THE FLAGRANCY QUALIFICATION HEARING AND THE DIRECT PROCEDURE", and its general objective is to propose a legislative reform to the reform already approved and by come into force, on art. 99 of Official Supplement No. 107, of 2019, which reforms the current art. 640 of the Comprehensive Organic Criminal Code, which establishes the new rules of direct procedure, in order to guarantee due process in the flagrante delicto qualification hearing, which will be achieved thanks to the use of scientific methods such as historical, analytical- synthetic and inductive-deductive. With this investigation, it will be possible to guarantee due process in the integral processing of the direct procedure.